INTERNATIONAL JUSTICE ON THE CASPIAN: ASSESSING AZERBAIJAN’S JOURNEY TOWARDS ICC STATUTE IMPLEMENTATION - Carrasco, S.H (International Journal of Political Science and International Relations (IJPSIR), 2023)
The International Criminal Court (ICC) has emerged as a cornerstone of the international legal landscape, exemplifying the evolution of global jurisprudence and the imperative for collective state action to address critical international concerns. Functioning as a universal treaty-based judicial entity, the ICC collaborates with national criminal justice systems to uphold international law and order. This paper traces the genesis of the ICC within the context of its antecedents, notably the ad hoc tribunals for the former Yugoslavia and Rwanda, whose efficacy and evenhandedness were questioned. The ad hoc tribunals faced allegations of partiality, particularly the tribunal for the former Yugoslavia, which was criticized for its perceived focus on the Serbs. This paper highlights the concerns raised regarding politicization and selectivity, contending that the ICC was established to rectify such deficiencies and bolster the global rule of law. The ICC’s underpinning legal foundation and its mandate have garnered significant support from numerous states. Unlike its predecessors, which were established by the UN Security Council, the ICC was instituted through a universal international treaty, the Rome Statute. This inclusive approach allows participating states to voluntarily extend the Court’s jurisdiction, fostering a more legitimate and equitable basis for its functioning. Drawing inspiration from the Charter and Judgment of the Nuremberg Tribunal and subsequent developments in international law, the ICC’s Statute amalgamates elements from diverse conventions and resolutions, enshrining principles of individual accountability for international crimes. A pivotal aspect of the ICC’s framework is its harmonization with national criminal justice systems, intervening only when domestic mechanisms falter or prove ineffective. By operating in tandem with national authorities, the ICC supplements their efforts and reinforces the enforcement of international law. This symbiotic relationship with national jurisdictions affords the ICC a dual role as a supportive adjunct and an autonomous mechanism, ensuring that accountability for grave international transgressions is not contingent upon the limitations of domestic systems. While the ICC has realized notable successes, exemplified by the conviction of individuals like Dominic Ongwen, challenges persist. Criticisms center around perceived biases and constraints on its jurisdiction. Nevertheless, the ICC’s enduring significance in the global battle against impunity remains undeniable. As a testament to the maturation of international legal norms, the ICC stands as an emblem of collective commitment to justice, reflecting the shared aspiration to combat the gravest crimes affecting the international community.